Hubungan Pengetahuan tentang Menstruasi dengan Perilaku Kesehatan Peserta Didik SMAN 2 Padang untuk Mengantisipasi Dismenorea Primer - Dhafa Rifiona Rahma; Ristiono Ristiono (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Students felt various complaints during menstruation, ranging from emotional ups and downs, dizziness and physical discomfort that interfered with daily activities such as lower abdominal pain, namely dysmenorrhea. Dysmenorrhea is menstrual pain in the lower abdomen that is felt by almost some women who are menstruating. The behavior experienced by students when they feel menstrual pain is related to the actions taken in seeking healing and anticipation before the pain interferes with activities. This study aims to determine the relationship between knowledge about menstruation and health behavior of students to anticipate primary dysmenorrhea. This type of research is a correlational descriptive research. The instruments used in this study were a knowledge test about menstruation and a health behavior questionnaire to anticipate primary dysmenorrhea. The population of this study were all female students of Class XI MIPA at SMAN 2 Padang. The research sample was 50 people using a purposive sampling technique. Based on the results of the research that has been done, it is known that the relationship between knowledge about menstruation and health behavior of students to anticipate primary dysmenorrhea is included in the sufficient category with a value of r = 0.441; with a tcount coefficient of 3.404 greater than the ttable coefficient of 2.01063. So, t count > t table so it can be concluded that there is a positive and significant relationship between the level of knowledge about menstruation and the health behavior of Class XI SMAN 2 Padang students to anticipate primary dysmenorrhea.